2016
DOI: 10.1007/978-3-319-42023-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Progress Towards Computational 3-D Multicellular Systems Biology

Abstract: Tumors cannot be understood in isolation from their microenvironment. Tumor and stromal cells change phenotype based upon biochemical and biophysical inputs from their surroundings, even as they interact with and remodel the microenvironment. Cancer should be investigated as an adaptive, multicellular system in a dynamical microenvironment. Computational modeling offers the potential to detangle this complex system, but the modeling platform must ideally account for tumor heterogeneity, substrate and signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 89 publications
(168 reference statements)
0
49
0
Order By: Relevance
“…For the piecewise quadratic force, the minimization was done jointly over µ R and the ratio m. The adhesive spring stiffness was then chosen as µ A = m × µ R . The values for r R and α where chosen according to Equations (12) and (14). Their values are stated here rounded to three decimals.…”
Section: Impact Of the Parameterization On The Radius Of A Monolayer mentioning
confidence: 99%
See 2 more Smart Citations
“…For the piecewise quadratic force, the minimization was done jointly over µ R and the ratio m. The adhesive spring stiffness was then chosen as µ A = m × µ R . The values for r R and α where chosen according to Equations (12) and (14). Their values are stated here rounded to three decimals.…”
Section: Impact Of the Parameterization On The Radius Of A Monolayer mentioning
confidence: 99%
“…Discrete cell-based models -independent of being on-or off-lattice -can be coupled to PDE models for simulating the concentration of chemical compounds in the cellular environment or even an ODE model for simulating intracellular dynamics [13,14,15]. An extensive review of cell-based models for general tissue mechanics can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Lawrence J. Ellison Center for Transformative Medicine, University of Southern California, Los Angeles, CA USA. 5 Intelligent Systems Engineering, Indiana University, Bloomington, IN USA. Figure 1 Sample 3-D cancer-immune simulation.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Cancerhost interactions dominate throughout these scales, including interactions between tumor cells and the vas-culature (hypoxic tumor cells trigger growth of new blood vessels; new but dysfunctional blood vessels supply further growth substrates and can promote metastasis), between tumor cells and stromal cells (tumor cells can prompt tissue remodeling that facilitates tissue invasion), and between tumor cells and the immune system (immune cells can kill tumor cells, but tumor cells can co-opt inflammation to promote their survival). See the reviews in [1,2,3,4,5,6]. When designing and evaluating new cancer treatments, it is imperative to consider the impact on this complex multiscale cancer-host system.…”
Section: Introductionmentioning
confidence: 99%